2014
DOI: 10.1111/pce.12455
|View full text |Cite
|
Sign up to set email alerts
|

Application of heat stress in situ demonstrates a protective role of irradiation on photosynthetic performance in alpine plants

Abstract: The impact of sublethal heat on photosynthetic performance, photosynthetic pigments and free radical scavenging activity was examined in three high mountain species, Rhododendron ferrugineum, Senecio incanus and Ranunculus glacialis using controlled in situ applications of heat stress, both in darkness and under natural solar irradiation. Heat treatments applied in the dark reversibly reduced photosynthetic performance and the maximum quantum efficiency of photosystem II (Fv/Fm), which remained impeded for sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 71 publications
(137 reference statements)
4
42
0
Order By: Relevance
“…ferrugineum . Nonetheless, complete F v / F m recovery was observed for all species by the end of the warming treatment (Buchner et al ). These results are in agreement with the one reported by Shi et al () and allow inferring that the increase in Chl content because under warmer climate could translate into an enhancement of photosynthetic activity, plant growth and carbon assimilation in alpine species if there is no water limitation.…”
Section: Adaptation Responses To Abiotic Stresses In High‐mountain Plmentioning
confidence: 92%
See 2 more Smart Citations
“…ferrugineum . Nonetheless, complete F v / F m recovery was observed for all species by the end of the warming treatment (Buchner et al ). These results are in agreement with the one reported by Shi et al () and allow inferring that the increase in Chl content because under warmer climate could translate into an enhancement of photosynthetic activity, plant growth and carbon assimilation in alpine species if there is no water limitation.…”
Section: Adaptation Responses To Abiotic Stresses In High‐mountain Plmentioning
confidence: 92%
“…This indicates a higher adaptation capacity of perennial herbs to shifts in temperature, in comparison to non‐perennial species (Shi et al ). Furthermore, Buchner et al () have reported the significant effect of rising temperatures on photosynthetic parameters in Senecio incanus, Ranunculus glacialis and Rhododendron ferrugineum . The F v / F m showed no significant decrease under high temperature in the two species, although a considerable reduction of the values for this parameter was observed in Rh.…”
Section: Adaptation Responses To Abiotic Stresses In High‐mountain Plmentioning
confidence: 99%
See 1 more Smart Citation
“…A purpose‐built ‘heat tolerance testing system’ (HTTS) was recently developed that allows for the measurement of responses in intact plants in situ under controlled conditions in the field, without removing plants from their natural habitat (Buchner et al ). Using the HTTS, it was shown that light during short‐term heat exposure may have a positive effect on heat tolerance and photosynthetic performance (Buchner et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…High temperature is an important abiotic stress which is becoming most limiting factor for normal plant growth and development, especially under climate change scenario which is projected to the average temperature be increased 1.1 °C in the last 50 yr (Ding et al, 2007). High temperature imparts its injurious effects on photosynthesis (Buchner et al, 2015), disrupts the overall balance of the metabolic processes, leading to the over production of reactive oxygen species (ROS) which ultimately causes oxidative damage to the plant cells (Larkindale et al, 2005). The enhanced synthesis of ROS causes lipid peroxidation of biological membranes, denaturation of proteins and damage to the nucleic acid eventually disturbing homeostasis (Mittler, 2002).…”
Section: Introductionmentioning
confidence: 99%